Physical activity as a protective factor in the mood of children and adolescents: association with overweight and obesity - Andrade, Alexandro; dos Santos, Keyla Mara; D’Oliveira, Anderson; Claudino, Verônica Maria; da Cruz, Whyllerton Mayron (Frontiers in Pediatrics, 2025)
IntroductionSedentary children and adolescents are more susceptible to developing diseases, obesity and psychological disorders, but little is known about the relationship between physical activity (PA), body mass index (BMI) and mood state in this population.MethodsThis is a cross—sectional study with the participation of 2,757 students, aged between 10 and 19 years. The Brunel Mood Scale—BRUMS was used to assess the dimensions of tension, depression, anger, vigor, fatigue and mental confusion, and the PA questionnaire for children and adolescents was used to assess the practice of PA.ResultsThere was a significant difference between the eutrophic and overweight BMI groups for the mood states of depression (p = 0.004) and vigor (p = 0.047). On the other hand, the overweight (4.06 ± 4.3) and obese (3.85 ± 4.0) groups had the highest rates of depression. It was observed that a higher BMI was associated with depression, anger and fatigue in children and adolescents and that PA can explain 39% of vigor in this population (F = 103.062, p = 0.000; R2 = 0.039). Active children and adolescents had twice as much vigor as inactive ones. There were differences between males and females, and between active and inactive individuals, in depression, anger, vigor, fatigue and confusion. There was a tendency for overweight and obese children and adolescents to have higher rates of depression when compared to underweight or normal-weight individuals.ConclusionThe practice of physical activity (PA) was shown to have a positive effect on mood, with active children and adolescents reporting lower levels of depression, anger, fatigue, and confusion, and higher levels of vigor. These findings underscore the importance of PA as a protective factor against mood disturbances in this population, highlighting its potential role in improving emotional well-being.